2009
DOI: 10.1371/journal.ppat.1000506
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Patterns of EBV Infected EBNA-3A Positive and Negative Human B Lymphocytes

Abstract: The genome of Epstein-Barr virus (EBV) encodes 86 proteins, but only a limited set is expressed in EBV–growth transformed B cells, termed lymphoblastoid cell lines (LCLs). These cells proliferate via the concerted action of EBV nuclear antigens (EBNAs) and latent membrane proteins (LMPs), some of which are rate limiting to establish a stable homeostasis of growth promoting and anti-apoptotic activities. We show here that EBV mutants, which lack the EBNA-3A gene, are impaired but can still initiate cell cycle e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
150
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(168 citation statements)
references
References 54 publications
16
150
2
Order By: Relevance
“…3A). This observation is in agreement with previous studies where LCLs derived from viruses with EBNA 3A deleted were found to express higher levels of ADAM28 than control LCLs (14). However, since only one EBNA 3A-and one EBNA 3B-expressing cell line were available for analysis, the individual effects of these proteins on ADAM28 expression requires further verification.…”
Section: Resultssupporting
confidence: 92%
“…3A). This observation is in agreement with previous studies where LCLs derived from viruses with EBNA 3A deleted were found to express higher levels of ADAM28 than control LCLs (14). However, since only one EBNA 3A-and one EBNA 3B-expressing cell line were available for analysis, the individual effects of these proteins on ADAM28 expression requires further verification.…”
Section: Resultssupporting
confidence: 92%
“…The experiments described here investigate the underlying biochemical mechanisms and significance of initial findings that conditional EBNA3A or EBNA3C inactivation in LCLs induces G 1 growth arrest, which for EBNA3C is associated with induction of CDKN2A p16 INK4A expression, consistent with the possibility that EBNA3A and EBNA3C's essential role is to repress CDKN2A p16 INK4A (5)(6)(7)(8). EBNA3A, EBNA3B, and EBNA3C likely arose as a consequence of gene triplication, after the evolution of EBNA2 and EBNALP (9).…”
supporting
confidence: 61%
“…Because conditional E3AHT inactivation in LCLs has similar effects on LCL growth and p16 INK4A is also elevated in EBNA3A knockout LCLs relative to wild-type LCLs (5,7,8), EBNA3A may also have a role in p16 INK4A and p14 ARF repression. Indeed, incubation of E3AHT LCLs in media without 4HT, resulted at day 6 in substantially reduced E3AHT, slowed cell growth, increased p16 INK4A and p14 ARF protein expression, and ∼1.4-fold significantly increased p16 INK4A and p14 ARF RNA levels ( Fig.…”
Section: Ebna3c Inactivation Changes Chromatin At the P16 Ink4a Locusmentioning
confidence: 99%
“…To consider the potential overlap of EBNA3C and EBNA3A transcriptional effects, we compared EBNA3C effects on RNA levels with putative EBNA3A effects, which have been assessed by comparison of RNA levels in LCLs with RNA levels in B cells grown on feeder cells after infection with an EBNA3A-negative EBV (53). Overall, 52 genes were significantly regulated by both EBNA3C and EBNA3A, with a P value of <3 × 10 −23 ( Fig.…”
Section: Ebna3c-regulated Genes Overlap With Ebna2-and Ebna3a-regulatedmentioning
confidence: 99%